Preliminary Real-World Outcomes of Adjuvant Immunotherapy in Resected Esophageal Cancer: A Retrospective Study from Taiwan - Chia Liu; Yi-Chen Yeh; Ling-I Chien; Chien-Sheng Huang; Han-Shui Hsu; Po-Kuei Hsu (Journal of Chest Surgery, 2025)
Background: The CheckMate 577 trial demonstrated that adjuvant nivolumab improves disease-free survival in patients with resected esophageal cancer following neoadjuvant chemoradiotherapy. This study aimed to evaluate real-world outcomes associated with adjuvant immunotherapy. Methods: Patients with esophageal cancer and residual pathological disease who underwent neoadjuvant therapy followed by surgical resection between January 2019 and February 2024 were retrospectively analyzed. Participants were grouped by adjuvant treatment received: no adjuvant therapy, adjuvant immunotherapy (AI), or adjuvant chemotherapy (AC). Primary outcomes included overall survival (OS) and recurrence-free survival (RFS). Subgroup analyses were performed for patients meeting CheckMate 577 eligibility criteria and those with pathological node-positive (ypN+) status. Results: The study included 127 patients (mean age: 60 years; male: 86%): 23 received AI, 36 AC, and 68 received no adjuvant therapy. There were no significant differences in OS between AI and AC groups (median OS [mOS]: 34 months vs. 34 months; p=0.81), nor in RFS (median RFS [mRFS]: 15 months vs. 16 months; p=0.94). In the CheckMate 577-eligible subgroup (n=68), OS and RFS were similar between AI and AC groups (mOS: 25 months vs. 47 months; p=0.16; mRFS: 19 months vs. 20 months; p=0.74). Likewise, among ypN+ patients (n=54), no significant differences in OS or RFS were noted between AI and AC (mOS: 34 months vs. 31 months; p=0.74; mRFS: 9.5 months vs. 14 months; p=0.89). Conclusion: AI did not demonstrate a significant survival advantage compared to AC, even in patients meeting CheckMate 577 criteria or those with ypN+ status. Identifying the optimal adjuvant treatment for esophageal cancer remains a challenging and evolving issue.